A deputy’s request for information containing bank secrecy in Ukraine: an urgent issue of the present - K. V. Kysylova; D. V. Korobtsova (Law and Safety)
The article is devoted to the study of the peculiarities of a People’s Deputy of Ukraine’s request to banking institutions with the purpose of obtaining information containing bank secrecy.